Laos-China Cooperation in the Construction of High Speed Railway: A Perspective of Foreign Policy - Rizqiyah, Emilda; Prasodjo, Haryo; Pradana, Hafid Adim (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article addresses Laos' motivations for working with China on their proposed high-speed train and railway projects. Due to its lack of access to land channels, Laos chooses to conduct its commercial and tourism cooperation with China through the BRI initiative, which is China's foreign strategy in establishing relations with ASEAN nations. We use the theory of foreign policy (FPA) to address several justifications for Laos' participation in China's high-speed rail and fast train projects. We found five reasons why Laos should join China: First, China's location allows for communication with landlocked Laos through the construction of the Laos High Speed Railway; second, China's demographics can help Laos become more prosperous; Â third, Laos relies on China's natural resources to match the Lao population's consumption level; fourth, China's political system has improved bilateral ties with Laos giving Laos hope that long-term collaboration may be created with China through the construction of transportation infrastructure in the form of the China-Laos High-Speed Railway; and fifth, Laos's economic prowess can assist with commerce and provide funding for growth between Laos and China.